2011
DOI: 10.1093/jxb/erq402
|View full text |Cite
|
Sign up to set email alerts
|

The role for the exocyst complex subunits Exo70B2 and Exo70H1 in the plant–pathogen interaction

Abstract: Recently, the octameric vesicle-tethering complex exocyst was found in plants and its importance for Arabidopsis morphogenesis was demonstrated. Exo70 exocyst subunits in plants, unlike in yeasts and mammals, are represented by a multigene family, comprising 23 members in Arabidopsis. For Exo70B2 and Exo70H1 paralogues, transcriptional up-regulation was confirmed on treatment with an elicitor peptide, elf18, derived from the bacterial elongation factor. Their ability to participate in the exocyst complex forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
172
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(185 citation statements)
references
References 44 publications
9
172
3
1
Order By: Relevance
“…We also confirmed via Y2H that the full-length PUB22 was able to interact with the full-length Exo70B2 (see Supplemental Figures 1B and 1C online). Exo70B2 also interacts with other subunits of the exocyst complex, supporting its role as a functional component of the exocyst complex (Pecenková et al, 2011).…”
Section: Pub22 Interacts With the Exo70b2 Subunit Of The Exocystmentioning
confidence: 84%
See 1 more Smart Citation
“…We also confirmed via Y2H that the full-length PUB22 was able to interact with the full-length Exo70B2 (see Supplemental Figures 1B and 1C online). Exo70B2 also interacts with other subunits of the exocyst complex, supporting its role as a functional component of the exocyst complex (Pecenková et al, 2011).…”
Section: Pub22 Interacts With the Exo70b2 Subunit Of The Exocystmentioning
confidence: 84%
“…This expansion suggests that plants have evolved functionally specialized Exo70 genes (Zárský et al, 2009). Accordingly, a recent report demonstrated that Arabidopsis Exo70B2 and Exo70H1 genes are induced in response to pathogens and PAMPS and are genetically necessary for a functional immune response (Pecenková et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, PRA1s have been linked to vesicle trafficking and fusion (Heo et al, 2010;Lee et al, 2011). However, similar to ACD11 and XBAT35.2, the interacting AtPRA1.Fs may be involved in plant immunity as components of the vesicletrafficking system are actively engage in mounting defense against pathogens (Frei dit Frey and Robatzek, 2009;Nomura et al, 2011, Pecenková et al, 2011Stegmann et al, 2012). Although the significance of the interaction between AtPRA1.Fs, XBAT35.2, and ACD11 needs to be explored, the interaction provides further support for the Golgi localization of XBAT35.2.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Matchmaker GAL4 Two-Hybrid System 3 (Clontech) following the manufacturer's instructions. We used constructs prepared by Hála et al (2008), Fendrych et al (2010, and Pecenková et al (2011), and EXO70H4 cds was amplified from genomic DNA and subcloned into the pGBKT7 vector between NcoI and SalI using these primers: For_EXO70H4_NcoI, TTTCCATGGTGACGAGAAAAGCAATGAT; and Rev_EXO70H4_SalI, TTTGTCGACTTAGGACATGGATTGCCTTGAC. From this vector, EXO70H4 cds was recloned into pGADT7 using NdeI and XhoI restriction sites.…”
Section: Yeast Two-hybrid Assaysmentioning
confidence: 99%